Insights into impact of polar protic and aprotic solvents on bioactive features of 3-(Dimethylaminomethyl)-5-nitroindole: A DFT study and molecular dynamics simulations - Stève-Jonathan Koyambo-Konzapa; Berthelot S. D. Ramlina Vamhindi; Bekzod Khudaykulov; Peter A. Sidhom; Shahzeb Khan; Ashraf M. M. Abdelbacki; Alaa H. M. Abdelrahman; Mahmoud A. A. Ibrahim (PLoS ONE, 2025)
Polar protic and aprotic solvents can effectively simulate the maturation of breast carcinoma cells. Herein, the influence of polar protic solvents (water and ethanol) and aprotic solvents (acetone and DMSO) on the properties of 3-(dimethylaminomethyl)-5-nitroindole (DAMNI) was investigated using density functional theory (DFT) computations. Thermodynamic parameters retrieved from the vibrational analysis indicated that the DAMNI’s entropy, heat capacity, and enthalpy increased with rising temperature. Natural bond orbital computations elucidated the non-bonded interactions of DAMNI. DAMNI demonstrated promising nonlinear optical properties and chemical reactivity in water, with DMSO being the second most effective solvent. Frontier molecular orbitals and global descriptors confirmed the impact of solvents on intermolecular charge transfer. The docking estimations were conducted to predict the docking pose of DAMNI against ERα and EGFR, both of which are acknowledged for their significance in breast cancer treatment. Upon the docking outcomes, DAMNI revealed superior binding affinity against ERα (calc. –5.8 kcal/mol), in comparison with DAMNI against EGFR (calc. –4.7 kcal/mol). Eventually, molecular dynamics simulations (MDS) were carried out, followed by a binding energy computation utilizing the MM/GBSA approach. Upon the MM/GBSA//150 ns MDS, the DAMNI-ERα complex revealed lower binding energy than DAMNI-EGFR, with ΔGbinding values of −21.1 and −15.4 kcal/mol, respectively. Post-MD analyses showed outstanding constancy of the inspected complexes over 150 ns MDS.